Approaches to sustainable enterprise value - Miriam Jankalová; Jana Kurotová; Filip Bajza (Administrative Sciences, 2024)
Over the last two decades, business has taken a more systematic approach to understanding its impact on all of its stakeholders. Companies are striving to operate in a more sustainable way to improve the environmental, social and economic impact of their activities. Even today, the interest in determining the value of a company or parts of a company has not waned. As the economy continues to evolve, there are reasons and impulses that encourage companies to find out what their value is. The new approach is dependent on re-thinking value creation. There has been a growing understanding that sustainability requires a more comprehensive view of value that includes economic, social and environmental benefits. The aim of this paper is to propose a methodology for determining the sustainable value of an enterprise with respect to the factors influencing its value. This study is based on information that was gathered through an extensive literature review (research publications and research studies; the company's financial statements with notes) using Internet and research databases and the authors' own experiences. Methods of analysis, comparison, selection, abstraction, induction, deduction and statistics were used. The main findings of this study are as follows: the stakeholders require a company's sustainable value; the modification of the EVA method with the sustainable value approach brings a different perspective to the issue of determining the value of an enterprise. In addition to the positives, the proposed methodology has limitations that can be removed or improved with further research.
Keywords: 350; enterprise; methodology; sustainability; value